1993
DOI: 10.1002/bmc.1130070604
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of fenitrothion in liver, kidney and brain of rat

Abstract: The metabolic fate of fenitrothion, O,O-dimethyl-O-(3-methyl-4-nitro phenyl) phosphorothioate, was investigated in rat tissues during the first 24 hours following the intramuscular administration of the pesticide in the animal. High performance liquid chromatography (HPLC) of the pesticide and its metabolites formed in liver, kidney and brain showed the time-dependent sequential conversion of the pesticide into three major metabolites. These metabolites were separated and purified to homogeneity by HPLC and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This result agrees with some previous reports (35)(36)(37) which noted that, in adult rats, the insecticide is metabolized to phosphorothioate and dimethylphosphate compounds. While compound VI represented the main substance in collected urine in free and conjugated form besidetraces of compounds VII and VIII in case of pirimiphos-methyl.…”
Section: Bioavailability To Ratssupporting
confidence: 94%
“…This result agrees with some previous reports (35)(36)(37) which noted that, in adult rats, the insecticide is metabolized to phosphorothioate and dimethylphosphate compounds. While compound VI represented the main substance in collected urine in free and conjugated form besidetraces of compounds VII and VIII in case of pirimiphos-methyl.…”
Section: Bioavailability To Ratssupporting
confidence: 94%
“…Oxidative stress is known to cause a disruption of the oxidant–antioxidant balance leading to alterations of cellular macromolecules, disturbance in cell function and eventually can lead to cell death . In addition, fenitrothion inhibits acetylcholinesterase activity, thus disrupting the nervous system and causes conformational changes in liver and kidney cells of rats with complete damage of the nuclear membrane, total loss of nuclear intactness, and abnormally enlarged smooth endoplasmic reticulum …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to pesticides caused hepatotoxicity (Kalender et al, 2010), hematotoxicity (Durak et al, 2009), genotoxicity (Giri et al, 2002). In addition, OPIs can alter antioxidant enzyme activities and increase the production of free radicals in different tissues including the liver (Kumar et al, 1993); (Hazarika et al, 2003), brain (Kumar et al, 1993); (Brocardo et al, 2005) and kidney (Kumar et al, 1993); (Possamai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%